A política dos afetos: uma análise da relação obra-corpo-mundo como produção de potência de vida - Oliveira, Clayton de Moura (2019)
This dissertation discusses the affections that the works of art negotiate in the encounter with the bodies. It is a question of understanding how the action of such affections is capable of promoting a variational policy, which enables the bodies a unique movement that create new ways of transiting in life and in the world. The study emerges from the processes of experimentation that some works of contemporary art catalyzed in the body-scribe in movements of intense estrangement with the aesthetic device of art, which opened the field of possibilities for the reinvention of life, displaced from the dominant devices. The research is based on the concept of affection elaborated by Benedictus de Spinoza, especially in the contemporary reading of Gilles Deleuze, Felix Guattari and Brian Massumi. In effecting the affective-political dissection of the body-work relationship under study, a cartography of the body-scribe experiments was carried out through affections and sensations elicited by the encounter with the works of David Glat, in particular with the way his photographs reorganized the baroque in contemporary visuality; in several works by Hélio Oiticica, mainly focusing on the production of singularity in the advent of the body-invention in his works and in the process of sublimation of color that launches in space-time a coloring atmosphere in the suprassensorial haptic; and finally, we analyze the scenic-choreographic poetics of the dance show De-Vir, by Cia Dita, regarding the dissolution of the boundaries between the human and the animal and the emergence of the animal becoming. The affective actions of the works pointed to a virtual composition in the body-work-world relation, in the agency of singularities that make possible the creation of the new in the expression of bodies in the world.